Tingkat Kepatuhan Syariah di Lembaga Keuangan Syariah - Sepky Mardian (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2015)
This study aimed to evaluate the degree of implementation of syariah compliance inIslamic banks in Indonesia toward 3 aspects i.e Syariah Supervisory Board (SSB),product and financial report. The study was analyzed by exploratoring those aspects inIslamic banks. The study found several critical issues on syariah compliance towardSSB regarding the independence, multi-served position of SSB, competences andsyariah audit. The large scale of murabahah in Islamic bank financing that also wascaused by depositors paradigm on savings and the issue on murabahah that waspracticed differently to its basic concept are the critical issues on products. Finally,regarding to financial reporting such as income smoothing on profit distribution, lackof syariah competences of the independent auditor and treatment of murabahahmargin.